Hox control of organ size by regulation of morphogen production and mobility. - Crickmore, M.A.; Mann, R.S. (Science, 2006)
Selector genes modify developmental pathways to sculpt animal body parts. Although body parts differ in size, the ways in which selector genes create size differences are unknown. We have studied how the Drosophila Hox gene Ultrabithorax (Ubx) limits the size of the haltere, which, by the end of larval development, has approximately fivefold fewer cells than the wing. We find that Ubx controls haltere size by restricting both the transcription and the mobility of the morphogen Decapentaplegic (Dpp). Ubx restricts Dpp's distribution in the haltere by increasing the amounts of the Dpp receptor, thickveins. Because morphogens control tissue growth in many contexts, these findings provide a potentially general mechanism for how selector genes modify organ sizes.